New data on spiders (Arachnida, Aranei) of Kamchatka, Russia - Marusik Yuri M.; Nekhaeva Anna A. (Pensoft Publishers, 2022)
Since 1885 and for almost a century the Kamchatka Peninsula had been a region of Russia east of the Urals with the best studied spider fauna. Currently, Kamchatka can be considered the least studied Siberian region. In this paper, we have provided a brief overview of Tatyana V. Pavlenko's spider collection compiled in Kamchatka in 1988-1992. A species list contains 108 species belonging to 15 families, of which 25 species, five genera and the family Titanoecidae are new to the spider fauna of Kamchatka. Walckenaeria subspiralis Millidge, 1983 is recorded from the Palaearctic Region for the first time. Kolymocyba petrophila Eskov, 1989 previously known from Magadan Area only is illustrated to provide more detail data about its morphology. The female of Micaria yeniseica Marusik & Koponen, 2002 that was previously known from the holotype male from the middle reaches of Yenisei River only is described for the first time. Two species – M. yeniseica and Zelotes azsheganovae Esyunin & Efimik, 1992 – significantly extended their known range to the east. Based on new data, a total number of the spider species known from Kamchatka has extended to 273.